2001
DOI: 10.1016/s0550-3213(01)00188-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fixed-end strings and the off-shell disk amplitude

Abstract: An exact integral expression is found for the amplitude of a Bosonic string with ends separated by a fixed distance R evolving over a time T between arbitrary initial and final configurations. It is impossible to make a covariant subtraction of a divergent quantity which would render the amplitude non-zero. It is suggested that this fact (and not the tachyon) is responsible for the lack of a continuum limit of regularized randomsurface models with target-space dimension greater than one. It appears consistent,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…It is well-known [26,27,28] how this potential is calculable for the Nambu-Goto string, including the Lüscher term. Then the most convenient choice is to parametrize the string world-sheet by the coordinates along the T -and R-axes, which are conformal.…”
Section: Remark On the Area Law For Large Loops In Qcdmentioning
confidence: 99%
“…It is well-known [26,27,28] how this potential is calculable for the Nambu-Goto string, including the Lüscher term. Then the most convenient choice is to parametrize the string world-sheet by the coordinates along the T -and R-axes, which are conformal.…”
Section: Remark On the Area Law For Large Loops In Qcdmentioning
confidence: 99%
“…In[52] some words of caution were raised regarding the use of ζ-function regularization for the string with the present boundary conditions. However, in[26] it was shown that in the Polyakov loop correlator geometry, where open strings have very similar boundary conditions, the results of this procedure are perfectly consistent.…”
mentioning
confidence: 99%
“…In Ref [32]. some interesting words of caution were raised regarding the use of ζ-function regularization for the string with the present boundary conditions 5.…”
mentioning
confidence: 99%